Kepemimpinan Hindu Dalam Membangun Manusia Seutuhnya - I Nyoman Nadra (Kamaya: Jurnal Ilmu Agama, 2022)
Humans outwardly continue to develop and this development does not only cause positive impacts but also negative impacts accompanying human life individually and socially. Humans are naturally a leader for themselves and other individuals, but not all humans are aware of this, of course we need a concept or the right footing, in order to awaken the spirit of leadership in oneself as a whole human being based on dharma. The purpose of this research is to know and be able to apply the concept and contextual Hindu leadership in building a whole person. This research uses the research method of Library Research, which is qualitative in nature, with two data analysis strategies, namely the qualitative descriptive analysis strategy model and the verification analysis strategy. The development of Hindu leadership science is broadly sourced from Nitisastra as a leadership science. Nitisastra emphasizes the purpose of human life to improve balanced physical and spiritual well-being in the life of a whole person. In addition to Nitisastra, there is literature containing values ​​and leadership teachings known as Geguritan Niti Raja Sasana. Whole human beings based on Hindu leadership apply the concept of Asta Brata which is the eight basic mental attitude for a leader in carrying out the dharma of religion and the dharma of the state. The conclusion from the results of this study is that as a human being, it is necessary to understand the teachings of Hindu leadership that have been contained in the nitisastra and geguritan niti raja sesana literature by applying the Hindu leadership concept in everyday life in order to build a complete human being that is relevant to the goals of Hinduism. namely to achieve Jagadhita and Moksha.